Review of nematode parasites reported from Indian freshwater fishe (Zoological Records and Reviews, 2022)
Nematode parasites (Phylum Nematoda) constitute the most speciose and ecologically ubiquitous helminth groupinfecting freshwater fishes globally, with approximately 2,400 described species documented from fish hosts worldwide.In India, despite the exceptional diversity of freshwater fish hosts -- with over 930 species across multiple biogeographicprovinces -- systematic review of fish-parasitic nematodes has not been undertaken since the early monographiccontributions of Karve (1941) and Pande (1938-1939). This review synthesises published records of nematode parasitesfrom Indian freshwater fishes from 196 studies spanning 1938 to 2021, covering all major biogeographic zones and hostfamilies. A total of 284 nematode species belonging to 68 genera and 24 families are documented from Indian freshwaterfish hosts, representing the most comprehensive national synthesis to date. The families Capillariidae (48 species),Anisakidae (38 species), and Gnathostomatidae (28 species) are the most species-rich. Host specificity analysisindicates that 42.3% of documented species are host-specific at the genus level. The Gangetic plain fish fauna harboursthe most intensively studied nematode diversity (124 species), while the Western Ghats and northeastern Indian fishfaunas are comparatively undersampled. Zoonotic species -- nematodes with documented potential for human infection-- are identified in 18 species across four families. Updated nomenclature, host records, and geographic distribution data are provided for all documented species.
Keywords: review; taxonomy; zoonotic nematodes; host specificity; helminthology; Anisakidae; Capillariidae; Indian freshwater fishes; Nematoda; fish parasites